1994
DOI: 10.1080/02681219480000281
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis: clusters and sources?

Abstract: Clusters of invasive infection with Aspergillus fumigatus are known to be associated with building works but studying the epidemiology has been hampered by the lack of a reliable typing system. A combination of three typing systems; silver staining of sodium dodecyl sulphate-polyacrylamide gels, immunoblot fingerprinting, and random amplification of polymorphic DNA (RAPD) was applied to seven cases on a haematology unit. The results show three of the patients to have indistinguishable isolates, suggesting a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
1
20
1
3
Order By: Relevance
“…Thus, the global diversity suggests that strains are adapted to a local environment and that the epidemiology of A. fumigatus should be studied independently within each geographic area. This situation may be the result of local selective pressure (24), including climate, environmental adaptation, and therapeutic selection, as previously suggested (12,23). A combination of several typing methods was able to discriminate among strains to a greater extent than the same typing methods used separately.…”
Section: A Fumigatus (3)mentioning
confidence: 82%
“…Thus, the global diversity suggests that strains are adapted to a local environment and that the epidemiology of A. fumigatus should be studied independently within each geographic area. This situation may be the result of local selective pressure (24), including climate, environmental adaptation, and therapeutic selection, as previously suggested (12,23). A combination of several typing methods was able to discriminate among strains to a greater extent than the same typing methods used separately.…”
Section: A Fumigatus (3)mentioning
confidence: 82%
“…First, PCR components and parameters and DNA quality and gel electrophoresis duration are known to affect the reproducibility of RAPD, as does the discriminatory strength of selected primers (17,19,24). In our study, DNA quality does not seem to interfere with the RAPD patterns since no modification of the patterns was seen when a DNA extraction protocol currently used for RAPD was tested on 10 isolates (26).…”
mentioning
confidence: 83%
“…Similar results have been obtained in a more limited set of studies of nosocomial Aspergillus infection. In several of these studies, nosocomial aspergillosis cases in the same care units were caused primarily by unrelated strains (69,124,178), while in other studies, the same strain was cultured from the majority of patients in an intensive care unit (202,385). In two similar studies of Cryptococcus neoformans, no indications were obtained of single strains causing an outbreak (147) or of single strains causing infections in a particular hospital or geographical locale (256).…”
Section: Determining the Origin Of Nosocomial Infectionsmentioning
confidence: 99%
“…Even more disturbing are reports of variation due to the Taq enzyme source. Louden et al, who have used the RAPD methodology to fingerprint A. fumigatus isolates in a number of studies (202), reported that different lots of Taq polymerase resulted in great enough variability to generate what they termed "pseudoclusters" (201). Evidence was presented that one enzyme lot could not discriminate among isolates while the other could.…”
Section: Random Amplified Polymorphic Dna and Related Pcr-based Fingementioning
confidence: 99%
See 1 more Smart Citation